Evaluation of Nutritional and Phytochemical Profiles of Pumpkin Seed and Flesh (Cucurbita genus) Collections from Baringo, Uasin Gishu and Elgeyo Marakwet Counties - Tanui, M.; Binott, J. J.; Too, E. J.; Dangasuk, O. G. (Africa Environmental Review Journal, 2022)
Pumpkin (Cucurbita genus) is one of the indigenous crops grown globally. Cucurbits are nutrient rich vital food for subsistence farmers and urban consumers. There is currently little knowledge of nutritional, phytochemical and health benefits of pumpkins. This study aimed at evaluating nutritional and phytochemical profiles of 27accessions collected from Baringo, Uasin Gishu and Elgeyo Marakwet counties. Selection was based on physiological parameters. Atomic Absorption Spectroscopy and flame photometry determined quantities of mineral elements. Phytochemical contents were determined following the procedures of Harborne (1973), Obadoni and Ochuko (2001), Boham and Kocipai (1974) and Folin Denis Colometric method. Proximal compositions were determined using standard methods. SPSS Inc. software version 22.0 (p≤0.05), Duncans Multiple Range Test and Pearson correlations matrix were used in data analyses. Seeds had higher minerals than fruit flesh. (mg/100g) Ca 46.197±6.315, Zn 0.746±0.239, Cu 0.710±0.207, Fe 12.490±1.282, Mg 1.308±10.923, Mn 8.131±0.341, P, Na, K; 0.687±0.164, 103.339±1.362, 149.074±23.506 respectively. Fruit flesh had; Ca 21.751±4.604, Zn 0.086±0.033, Cu 0.070±0.020, Fe 6.920±1.052, Mg 0.367±7.917, Mn 5.633±0.099, Na 71.256±4.427, P 0.209±0.074, K 128.966±17.035. Significant positive correlations were found between: flavonoid in seed and alkaloid in flesh (r = 0.343), tannin in seeds and alkaloids in flesh (r = 0.326) and seed (r = 0.286); tannins in flesh and alkaloids in seed (r = 0.278; saponin in seed and alkaloid in flesh (r = 0.268);saponin in seed significantly correlated with tannin in flesh (r = 0.383) and saponin in seed(r = 0.343); Flavonoids in seed and flesh had significant negative correlation(r = -0.273). Highest proximal contents were observed in: Moisture; 8.162a (TUL 041) seeds, KAP 011 flesh (14.533a). Ash was 7.00a in KAP 003 seeds, CHEP 1 had 19.050a. Lipids were 46.757q in MEG 052 seeds while KAP 011flesh had 9.400a. Proteins in CHEP 2 seeds (38.424ab), 27.895a (EMS 225 flesh). Crude fibre (25.246a) in KAPS 022, 5.800a in RAN 1 flesh. Carbohydrate in NGE 064 seeds (69.217%), EMS 223 flesh (14.255%). CHEP 1 seeds, KAP 011 flesh are good sources of (P, K Na, and Ca). NGE 064 seeds and EMS 223 flesh are excellent sources of carbohydrates, CHEP 2 seeds and EMS 225 flesh are reliable sources of proteins. Breeders should consider pumpkins with high nutritional values to be used in formulating feeds and supplements for infants, expectant mothers and patients. The same will also be helpful in curbing malnutrition.